Endothelial PPARγ (Peroxisome Proliferator–Activated Receptor-γ) Protects From Angiotensin II–Induced Endothelial Dysfunction in Adult Offspring Born From Pregnancies Complicated by Hypertension. Issue 1 (July 2019) - Nair, Anand R.; Silva, Sebastiao D.; Agbor, Larry N.; Wu, Jing; Nakagawa, Pablo; Mukohda, Masashi; Lu, Ko-Ting; Sandgren, Jeremy A.; Pierce, Gary L.; Santillan, Mark K.; Grobe, Justin L.; Sigmund, Curt D.
Abstract : Preeclampsia is a hypertensive disorder of pregnancy associated with vascular dysfunction and cardiovascular risk to offspring. We hypothesize that endothelial PPARγ (peroxisome proliferator–activated receptor-γ) provides cardiovascular protection in offspring from pregnancies complicated by hypertension. C57BL/6J dams were bred with E-V290M sires, which express a dominant-negative allele of PPARγ selectively in the endothelium. Arginine vasopressin was infused throughout gestation. Vasopressin elevated maternal blood pressure at gestational day 14 to 15 and urinary protein at day 17 consistent. Systolic blood pressure and vasodilation responses to acetylcholine were similar in vasopressin-exposed offspring compared to offspring from control pregnancies. We treated offspring with a subpressor dose of angiotensin II to test if hypertension during pregnancy predisposes offspring to hypertension. Male and female angiotensin II–treated E-V290M offspring from vasopressin-exposed but not control pregnancy exhibited significant impairment in acetylcholine-induced relaxation in carotid artery. Endothelial dysfunction in angiotensin II–treated E-V290M vasopressin-exposed offspring was attenuated by tempol, an effect which was more prominent in male offspring. Nrf2 (nuclear factor-E2-related factor) protein levels were significantly elevated in aorta from male E-V290M offspring, but not female offspring compared to controls. Blockade of ROCK (Rho-kinase) signaling and incubation with a ROCK2-specific inhibitor improved endothelial function in both male and female E-V290M offspring from vasopressin-exposed pregnancy. Our data suggest that interference with endothelial PPARγ in offspring from vasopressin-exposed pregnancies increases the risk for endothelial dysfunction on exposure to a cardiovascular stressor in adulthood. This implies that endothelial PPARγ provides protection to cardiovascular stressors in offspring of a pregnancy complicated by hypertension and perhaps in preeclampsia. Abstract : Supplemental Digital Content is available in the text.